MS-150-10-f02-015: Letter from Beatrice Portsmouth - Portsmouth (Valdosta, GA: Valdosta State University Archives and Special Collections, 1895)
Letter from Beatrice Portsmouth [wife of the Newton Wallo, 6th Earl of Portsmouth], Dated March 2, to attend dinner at 2, Abbey Garden. This letter was hand delivered.
1 handwritten letter, 4 pages.
Keywords: Personal correspondence; Letters; Arnold, Edwin, Sir, 1832-1904; Poets--Correspondence; Nobility--England--Correspondence